Nitrogen Availability in Upland Soil Treated with Swallow Dropping - Normaulidia Normaulidia; Akhmad Rizalli Saidy; Fadly Hairannoor Yusran (Department of Soil, Faculty of Agriculture, Lambung Mangkurat University, 2022)
One of the problems in upland soils is poor in nutrient N. One effort to increase the availability of N in the soil is by providing swallow’s droppings which has a high N content. Thus, the purpose of this research was to determine the availability of N on upland soil was by applying swallow manure. This research employed Completely Randomized Design (CRD) with single factors (several levels of swallow’s manure: 0.0; 2.5; 5.0; 7.5; and 10.0 t ha–1). The availability of N in the soil was observed through the experimental column leaching, where 20 g of Ultisols was mixed with 20 g of quartz sand and swallow’s manure on a leaching column of 1-inch diameter and 20 cm height. Mineralized amounts of NH4+ and NO3– from the soil were determined by the percolation method (leaching) in every five days for 25 days. The results showed that the application of swallow’s manure increased the availability of total-N in the soil in the form of NH4+ and NO3–, and produced the release pattern of NH4+ and NO3– which was still relatively high until the end of the testing period. The results of this study demonstrate that application of swallow’s manure may be used as a slow-release fertilizer.